A heuristic model of socially learned migration behaviour exhibits distinctive spatial and reproductive dynamics. (12th July 2018) - MacCall, Alec D; Francis, Tessa B; Punt, André E; Siple, Margaret C; Armitage, Derek R; Cleary, Jaclyn S; Dressel, Sherri C; Jones, R Russ; Kitka, Harvey; Lee, Lynn C; Levin, Phillip S; McIsaac, Jim; et al.
Abstract: We explore a "Go With the Older Fish" (GWOF) mechanism of learned migration behaviour for exploited fish populations, where recruits learn a viable migration path by randomly joining a school of older fish. We develop a non-age-structured biomass model of spatially independent spawning sites with local density dependence, based on Pacific herring ( Clupea pallasii ). We compare a diffusion (DIFF) strategy, where recruits adopt spawning sites near their natal site without regard to older fish, with GWOF, where recruits adopt the same spawning sites, but in proportion to the abundance of adults using those sites. In both models, older individuals return to their previous spawning site. The GWOF model leads to higher spatial variance in biomass. As total mortality increases, the DIFF strategy results in an approximately proportional decrease in biomass among spawning sites, whereas the GWOF strategy results in abandonment of less productive sites and maintenance of high biomass at more productive sites. A DIFF strategy leads to dynamics comparable to non-spatially structured populations. While the aggregate response of the GWOF strategy is distorted, non-stationary and slow to equilibrate, with a production curve that is distinctly flattened and relatively unproductive. These results indicate that fishing will disproportionately affect populations with GWOF behaviour.